Proverbs and Sayings in the Armenian-Kypchak Language: Semantic-Structural Analysis - Serikkazykyzy, A.; Avakova, R.A. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The study of proverbs and sayings in the Armenian-Kypchak language in comparison with current proverbs and sayings of the Turkic peoples is one of the most important and relevant topics in linguistics and the history of language. This article focuses on the scientific works of scholars who studied proverbs and sayings in the Armenian-Kypchak language and on works and research articles of a German scholar, Merxs Adalbert. Additionally, the methods of formation of proverbs and sayings used in the Armenian-Kypchak language will be determined and analyzed, comparing them with proverbs and sayings in the modern Kazakh language. Proverbs and sayings are a unique genre of expressive art of speech that conveys the centuries-old national identity and knowledge of any nation. Proverbs and idioms found in the Armenian-Kypchak language are one of the linguistic and cultural heritage, reflecting the depth and wisdom of the centuries-old history and culture of the Turkic peoples. A large number of proverbs and sayings of significant educational value in these written monuments proves that our ancestors, the Kypchaks, were wise, broad-minded, and educated. It is no coincidence that the vast majority of proverbs and sayings written in the Armenian-Kypchak language are still used in the same form. It symbolizes the deep-rooted culture of the Kazakh people.